Photonic Integrated Circuit Architecture for Radio-over-Fibre Applications - Hasan, Mehedi (Université d'Ottawa / University of Ottawa, 2015)
The aim of the research presented in this thesis is to develop photonic integrated circuit (PIC) for Radio-over-Fiber (RoF) application. As such, at the beginning of the thesis, a dual-function photonic integrated circuit for microwave photonic applications is proposed. The photonic circuit is arranged to have two separate output ports, and depending upon the RF input signal strength, it provides either tunable millimeter wave carriers by frequency octo-tupling of the RF signal or frequency up-conversion of a microwave signal from the electrical to the optical domain. The circuit exploits the intrinsic relative phases between the ports of multi-mode interference couplers (MMI) to provide all the static optical phases needed, hence drift free. In the middle of thesis, a generalized architecture having N parallel phase modulators driven electrically with a progressive 2π⁄N phase shift is analyzed. The proposed design is justified by computer simulation for N=8 architecture with properly determined optical phase shifts to generate frequency multiplication of an electrical signal. The front- and back-end of the circuit comprises 4×4 MMI couplers enclosing an array of four pairs of phase modulators and 2×2 MMI couplers. The proposed design for frequency multiplication requires no optical or electrical filters; the operation is not limited to carefully adjusted modulation indexes. Later on, a generalized approach for achieving frequency multiplication using two cascades MZM is presented. The proposed design consists of a Mach-Zehnder interferometer with each arm containing a pair of Mach-Zehnder modulators (MZM) in series as a means of optoelectronic frequency multiplication (octo-tupling and quattourviginti-tupling). The circuit requires no electrical or optical filters. There is no requirement to carefully adjust the modulation index to achieve correct operation of the octo-tupler. A comparison is made with an alternative functionally equivalent single-stage parallel MZM circuit discussed herein the thesis. Finally, the thesis describes the generation of the same magnitude but opposite sign high order single optical side band from its output ports by using a RF source. A single stage parallel Mach-Zehnder Modulator (MZM) and a two-stage series parallel MZM architecture is described and their relative merits and demerits discussed. As an illustration of a prospective application it is shown how the circuit may be used to transport radio signals over fibre for wireless access; generating remotely a mm-wave carrier modulated by digital IQ data. A detail calculation of symbol error rate is presented to characterise the system performance. A mathematical analysis is provided to describe the principle of operation for all the proposed design and validated by commercially available industrial standard simulation tool.
Keywords: Radio-over-Fibre; Photonic Integrated Circuit